2022
DOI: 10.1002/adma.202106370
|View full text |Cite
|
Sign up to set email alerts
|

P‐Doped NiTe2 with Te‐Vacancies in Lithium–Sulfur Batteries Prevents Shuttling and Promotes Polysulfide Conversion

Abstract: Lithium–sulfur (Li–S) batteries have been hindered by the shuttle effect and sluggish polysulfide conversion kinetics. Here, a P‐doped nickel tellurium electrocatalyst with Te‐vacancies (P⊂NiTe2−x) anchored on maize‐straw carbon (MSC) nanosheets, served as a functional layer (MSC/P⊂NiTe2−x) on the separator of high‐performance Li–S batteries. The P⊂NiTe2−x electrocatalyst enhanced the intrinsic conductivity, strengthened the chemical affinity for polysulfides, and accelerated sulfur redox conversion. The MSC n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
127
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(155 citation statements)
references
References 61 publications
1
127
0
Order By: Relevance
“…For instance, (a) During electrode charging and discharging, intermediates such as insulating S, Li, and soluble Li polysulfide will be produced, which induce a “shuttle effect” 48 . (b) The slow vulcanization reaction leads to the accumulation of products 49,50 . (c) Ion intercalation cause volumetric expansion, which results in structural deactivation 51 .…”
Section: Doping Mechanism Of Mxene/sulfur Compositementioning
confidence: 99%
“…For instance, (a) During electrode charging and discharging, intermediates such as insulating S, Li, and soluble Li polysulfide will be produced, which induce a “shuttle effect” 48 . (b) The slow vulcanization reaction leads to the accumulation of products 49,50 . (c) Ion intercalation cause volumetric expansion, which results in structural deactivation 51 .…”
Section: Doping Mechanism Of Mxene/sulfur Compositementioning
confidence: 99%
“…In view of the above barriers, multiple methods have been provided to overcome these bottlenecks, such as constructing sulfur hosts, designing functional interlayers, optimizing electrolyte constituents, protecting lithium metal anodes and so forth. [12][13][14][15][16] To date, numerous efforts have mainly focused on the research of sulfur-based composite cathode materials, favorably maintaining the structural integrity of the entire electrode. Notwithstanding the shuttle effect of LiPSs which can be partly buffered, the limited active spots and internal spaces will bring about the accumulation of LiPSs, which will give rise to the structural collapse of the host materials.…”
Section: Introductionmentioning
confidence: 99%
“…6 To date, researchers have come up with many effective methods to solve these problems by employing carbon materials to enhance the conductivity and store sulfur as host materials, 7,8 adding the catalytic materials (metal oxides/ suldes, MOF, etc.) to promote the reaction kinetics, [9][10][11] optimizing the composition of the electrolyte to increase the stability of polysuldes, 12,13 and functionalizing the separator to inhibit the mobility of the polysuldes 8,14 as well as interlayers. [15][16][17] Recent works found that the interlayer could suppress the shuttle effect of polysuldes by physical, chemical, or physicochemical inhibition, displaying the noteworthy advantages as follows: 18,19 rst of all, the high conductivity derived from the addition of carbon materials (e.g., micro/ mesoporous carbon, CNTs, graphene, and porous biomaterials [20][21][22] ) allows sulfur to fully react and deliver high specic capacity; secondly, the chemical adsorption and catalytic effect from the functional materials effectively decreases the mobility of polysuldes, enhances the reaction kinetics, and allows the batteries to display high capacity and stable cycling; thirdly, the interlayer could simplify the cathode preparation process by avoiding further thermal energy consumption.…”
Section: Introductionmentioning
confidence: 99%